Study on the Treatment of Soybean Product Wastewater by Heterotrophic Nitrification-Aerobic Denitrification Acinetobacter - Nunes, Markus; Dantas, Javid; Sommer, Stacey (Journal of Green Energy and Environmental Engineering, 2025)
Soybean product wastewater (SPW) is organic wastewater generated during the processing of soybean products. Soaking, pulping, boiling, pressing and fermentation load SPW with high organic, N and P content, rendering it easily putrescible and malodorous. If discharged directly without treatment, it will cause serious harm to the receiving environment and human health. Heterotrophic Nitrification-Aerobic Denitrifying Microorganisms (HNADMs) have significant advantages in treating high-nitrogen organic wastewater, but there is currently no research report on using Heterotrophic Nitrification-Aerobic Denitrification (HN-AD) strains to treat SPW. Therefore, this study screened HN-AD strains from epiphytic aggregates of cyanobacteria in Taihu Lake through enrichment culture and gradient dilution-plate streaking, and optimized the process conditions for SPW using methods such as single-factor controlled variable method and response surface design experiments. On this basis, combined with molecular biology techniques such as whole-genome scanning, high-throughput sequencing, and functional gene polymerase chain reaction (PCR) amplification, the nitrogen removal pathways of HNADMs were explored. The main results are as follows: (1) With the existing HN-AD strain Acinetobacter CW-1 treating 3.3-fold-diluted SPW at 25 °C, 240 rpm, pH 5.26 and no external carbon, simultaneous removal of NH₄⁺-N, DTN, DTP and COD reached 99.4 %, 85.3 %, 28.0 % and 60.0 %, respectively. (2) Genome and HN-AD gene scans show strain CW-1 funnels NH₄⁺-N through three routes: GDH, GS-GOGAT, and the full HN-AD chain (NH₄⁺→NH₂OH→NO₂⁻→NO₃⁻→NO₂⁻→NO→N₂O/N₂).